Gray - Fouché, James De Clerque (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a crime fiction novella. I'm moved by the idea of developing feasible, relatable characters with flaws "“ a staple of the crime fiction genre. I also appreciate how crime serves as a platform from which to launch into human drama, the way James Ellroy does in The Black Dahlia. While my protagonist endures trials on a near Jobian scale, the narrative meditates on the consequences of crime and conflict in a satirical way. Writers like Ross Macdonald, Raymond Chandler, Flannery O'Connor, China Miéville and Derek Raymond have inspired me with their sharp imagery and unconventional characterization techniques. These techniques accelerate the ease with which a reader can step into the shoes of any given narrator. Their writing is crisp, uncluttered and uncomplicated.
Keywords: Creative writing (Higher education) -- South Africa; Diaries -- Authorship; Detective and mystery stories, South African (English) 21st century; South African fiction (English) 21st century; South African essays (English) 21st century; English fiction 20th century History and criticism; American fiction African American authors History and criticism; American fiction 20th century History and criticism